Study of mechanical and physical properties of pineapple leaf fiber and coffee husk filler reinforced polymer composite using response surface method - Kinisa Wareso Abesho; Moera Gutu Jiru; Hirpa G. Lemu; Mohammed Abdulkedir Alfeki (Polymer Testing)
In the search for structural materials that are strong, lightweight, and cheap, pineapple leaf, which is rich in cellulose and relatively inexpensive, seems to have good potential reinforcement in yarn production. Pineapple leaf fibers (PALF) and coffee husk filler (CHF) can be new sources of raw materials for industries and can be potential for polymer reinforcement. This study fabricates composite samples using the hand layup method, and the Response Surface Methodology is used to optimize the experimental design. An analysis of variance determines the significance of variables and the interaction between them and responses. To assess mechanical characteristics (such as tensile, compression, flexural, and impact strength), and the physical properties like, thermogravimetric, water absorption, characterization, regression models are developed and statistically validated. The quadratic model is found to be the best fit for the tensile strength, flexural strength, impact strength, and water absorption models, while the two-factor interaction model is determined to be the best fit for the compression strength. The primary significant output parameter contributions in all responses are 28.497 % of PALF for tensile strength, 65.41 % of PALF for compression strength, 29.755 % of CHF for flexural strength, 84.454 % of PALF for impact strength, and 56.92 % of PALF for water absorption.